2014
DOI: 10.1111/jmi.12197
|View full text |Cite
|
Sign up to set email alerts
|

Calcium silicate cement‐induced remineralisation of totally demineralised dentine in comparison with glass ionomer cement: tetracycline labelling and two‐photon fluorescence microscopy

Abstract: Two-photon fluorescence microscopy, in combination with tetracycline labelling, was used to observe the remineralising potentials of a calcium silicate-based restorative material (Biodentine(TM) ) and a glass ionomer cement (GIC:​Fuji​IX) on totally demineralised dentine. Forty demineralised dentine discs were stored with either cement in three different solutions: phosphate buffered saline (PBS) with tetracycline, phosphate-free tetracycline, and tetracycline-free PBS. Additional samples of demineralised dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 37 publications
8
22
1
1
Order By: Relevance
“…But in the case of Theracal as its hydration was compromised migration of elements may be a more probable cause for the increase in opacity. This is in agreement with recent studies where remineralization was observed in dentine following the placement of hydraulic calcium silicate-based dentine replacement materials [24,25]. In one of the studies intact dentine was used and calcium ion transfer was shown to happen together with the formation of calcium phosphate at the interface [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…But in the case of Theracal as its hydration was compromised migration of elements may be a more probable cause for the increase in opacity. This is in agreement with recent studies where remineralization was observed in dentine following the placement of hydraulic calcium silicate-based dentine replacement materials [24,25]. In one of the studies intact dentine was used and calcium ion transfer was shown to happen together with the formation of calcium phosphate at the interface [25].…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with recent studies where remineralization was observed in dentine following the placement of hydraulic calcium silicate-based dentine replacement materials [24,25]. In one of the studies intact dentine was used and calcium ion transfer was shown to happen together with the formation of calcium phosphate at the interface [25]. In the other study [24] the dentine was demineralized with formic acid.…”
Section: Discussionsupporting
confidence: 89%
“…Atmeh's study on the remineralization potential of Biodentine and glass ionomer (Fuji IX), on completely demineralized dentin showed the mineral formation of Ca-P like Raman peak related to apatite and most florescence intensity was represented by Biodentine treated dentin (26). Like the present study, Biodentine represented matrix remineralization, intra and peritubular mineralization in BSE-SEM.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have demonstrated the formation of a mineral infiltration zone at the calcium silicate cement–dentin interface and the production of tag‐like extensions within dentin tubules (Atmeh et al, ; Li et al, ). The migration of minerals from the capping materials to the adjacent dentin may increase bond strength.…”
Section: Discussionmentioning
confidence: 99%